Internal consistency reliability of the P300 to novelty in infants: The influence of trial number and data loss due to artifacts. Issue 8 (16th November 2021) - Sandre, Aislinn; Panier, Lidia; O'Brien, Ashley; Weinberg, Anna
Abstract: The P300 is an event‐related potential component that reflects attention to motivationally salient stimuli and may be a promising tool to examine individual differences in cognitive‐affective processing very early in development. However, the psychometric properties of the P300 in infancy are unknown, a fact that limits the component's utility as an individual difference measure in developmental research. To address this gap, 38 infants completed an auditory three‐stimulus oddball task that included frequent standard, infrequent deviant, and novel stimuli. We quantified the P300 at a single electrode site and at region of interest (ROI) and examined the internal consistency reliability of the component, both via split‐half reliability and as a function of trial number. Results indicated that the P300 to standard, deviant, and novel stimuli fell within moderate to high internal consistency reliability thresholds, and that scoring the component at an ROI led to slightly higher estimates of reliability. However, the percentage of data loss due to artifacts increased across the course of the task, suggesting that including more trials will not necessarily improve the reliability of the P300. Together, these results suggest that robust and reliable measurement of the P300 will require designing tasks that minimize trial number and maximize infant tolerability.